Optimizing Regional Financial Management through the Transformation of the Digital Financial Information System in the Bekasi City Government - Anwar, Dian Mohamad; Emita, Isyana; Melyani, Melyani; Rahadjeng, Indra Riyana; Indrarti, Wahyu; Rafik, Ahmad; Sari, Dian Indah (University of Science and Computer Technology, 2026)
This research adopts an applied research approach conducted in November 2023 at the Bekasi City Government. Data were collected through observation, interviews, and literature study. The system development methodology follows the System Development Life Cycle (SDLC), including system analysis, system design, implementation, and maintenance. The proposed digital financial information system is developed in Java and integrated with a MySQL database to manage financial data, including revenue and expenditure, SPP (Payment Request Letters), and SPJ (Accountability Reports). The system design incorporates tools such as Context Diagram (CD), Data Flow Diagram (DFD), Entity Relationship Diagram (ERD), and flowcharts to ensure systematic and structured development. The implementation of the digital system is expected to improve the accuracy, timeliness, and relevance of financial information, facilitate faster report generation, and enhance financial transparency and accountability in regional governance. The findings indicate that the transformation of a digital financial information system significantly supports the optimization of regional financial management processes, minimizes reporting errors, accelerates data processing, and strengthens decision-making processes within the Bekasi City Government. Therefore, the digital transformation of financial systems is essential in supporting good governance and sustainable regional development.